Nickel and chromium levels in the saliva and serum of patients with fixed orthodontic appliances - (:unkn) unknown (My University, 2001)
The aim of this study was to evaluate the concentrations of nickel and chromium ions in salivary and serum samples from patients treated with fixed orthodontic appliances. A second aim of this study was to determine any significant changes in these concentrations during any period of the treatment time. Saliva and blood samples were collected from 100 patients ranging in age from 12 to 33 years. Twenty samples from each group were obtained. The groups were as follows: In the first group, saliva and blood samples were collected before insertion of the fixed appliances. In the second, third, fourth, and fifth groups, samples were collected at 1 week, 1 month, 1 year, and 2 years after appliance insertion. The serum was prepared by centrifuging the blood samples at 3000 rpm for 10 minutes. The fixed appliances consisted of an average of 4 bands and 20 bonded brackets. No palatal or lingual appliances welded to bands or extraoral auxiliary appliances were used. The spectrophotometric determinations were carried out using electrothermal atomic absorption spectrophotometry. The results indicated certain differences in the amounts of nickel and chromium released from fixed orthodontic appliances during different periods of treatment. The Mann-Whitney U-test from the SPSS statistics program was used to analyze the significance of the differences between no-appliance samples and those obtained with the appliances present. In the serum, there were statistically significant increases in ion concentration in the second-year groups. In saliva samples, nickel and chromium reached their highest levels in the first month and decreased to their initial level in the rest of the groups. It can be concluded that fixed orthodontic appliances release measurable amount of nickel and chromium when placed in the mouth, but this increase doesn't reach toxic levels for nickel and chromium in the saliva and serum.
Keywords: Adult; Female; Humans; Adolescent; Male; Child; Saliva; Nickel; Time Factors; Orthodontic Appliances; Statistics, Nonparametric; Biodegradation, Environmental; Chromium; Corrosion; Hypersensitivity; Spectrophotometry, Atomic